Readings on Ethnic Relations in a Multicultural Society : Promoting NATIONAL UNITY and the Practice of NOBLE VALUES - Muhammad Kamarul Kabilan, editor; Zaharah Hassan, editor; Abu Daud Silong, chief editor (Serdang : Fakulti Pengajian Pendidikan UPM, 2005)
Includes bibliographical references and index.